i-NPD app: a tech-driven and green innovation for creative learning in marketing - Yusof, Mahjabin; Ibrahim, Intanshahriza (2025)
This study explores the use of an innovative digital tool—the i-NPD App—to enhance learning in New Product Development (NPD), a key Marketing subtopic often challenging for students. Built with Power Apps, the i-NPD App provides interactive, structured guidance on the 8-step NPD process while promoting sustainability by reducing paper use. Tested with 20 Marketing students, post-surveys results showed unanimous agreement that the app improves understanding, presentation, and application of NPD. Some users noted a cluttered interface, prompting the development of a detailed instruction manual to enhance usability and learning outcomes.